Relações entre habilidades musicais e habilidades sociais em pessoas com Síndrome de Williams: perspectivas e limitações - Asnis, Valéria Peres (2014)
Music education is seen as a well organized pedagogical procedure of literacy and awareness, giving to individuals with special needs or not the possibility to deal with their difficulties and limitations and discover their limits and skills. Despite of the growth of the researches in the music education field investigating people with special needs, the researches that focus on Williams syndrome is reduced, and most of this researches are found in international works. In Brazil, only one research was found that associates the improve to hold attention in a child with Williams Syndrome (WS) and the musicalization process. Thus, the theme of this research is to analyze the impact of music education on social skills development in individuals with WS. The general goal of this study is to verify the results of a Music Education Program for teenagers with WS. As specific goals, this work aims to: 1) elaborate, apply and evaluate a music education program for individuals with WS, related to promote social skills; 2) note and analyze if it could identify indications of better social insertion that could be assign to music education dynamics that involves auditory and rhythm perception, pulsation, visual and auditory memory, among others, as part of the musical learning process. This is a field research with a qualitative and quantitative approach. Two teenagers with WS participate in this research. The data collection instruments used were: 1) Social Skills Form, Problematic behavior and academic competence (SSRS-BR) for parents and WS people, performed at three time points (pre-, mid- and post-intervention); 2) Musical skills evaluation for teenagers with WS performed before and after the intervention; 3) Field diary, that includes records made by the researcher at the end of each intervention. The program lasted for 13 weeks for one teenager and 9 weeks for the other, with a weekly class of approximately 30 minutes each. The Music Education Program was developed in the fields that the researcher considered relevant to music learning. Data analysis was done by comparing the answers given by Social Skills Form, Problematic Behavior and Academic Competence (SSRS-BR), the Music Evaluations, the review of the filming made during interventions and field diary notes.